Rádio para ouvir e assisitir: tendências e estratégias do radiojornalismo na plataforma Facebook. - Rangel, Caroline Barbosa (2019)
Inserted in the communicative process of remediation, and in a continuous changing, radio is present in the current context of creative industries media convergence, registering a new phase on Facebook. This study aims to analyze the communicative strategies used by radios that present journalistic content in programming, broadcasting live on the network platform and in the traditional channel, on the dial, and discuss whether the product presented on the social network can be considered radio. From the analysis of 26 radio programs, selected through a mixed exploratory methodology, the study dwells on the appropriation of television and interactive elements, coming from the social network, in the language used for dial and Facebook audiences. The process of remediation and hybridization of the media outlet were also analyzed. The intersection of theoretical discussions with data obtained through empirical research allowed to conclude that, by inserting different elements into Facebook programming, the radio empowers its presence in the context of media convergence and remediation, dialoguing with different platforms, while reiterates the concepts of contemporary radio, defined by Debora Lopez (2009) and Marcelo Kischinhevsky (2016), regarding its hypermediatic and expanded behaviors. Even though still in a gradual process, with the joining in of few broadcasters inserted in the treated scenario, the research, as a final point, suggests an idea of transmedia radio, given the remediated and multiplatform scenario.